Business communication challenge of small enterprises in Bangladesh - Bari, Md. Saiful (International Journal of Business, Management and Economics, 2020)
The relative SME share in manufacturing value added is a lot extended and estimated to fluctuate between 45 to 50 per cent of totaling value-added generated with the aid of way of practicable of the manufacturing industries sector. Further as important sources of new agency introduction and growing new entrepreneurial talents, these industries furnish the much wished dynamism and vitality to the national economy. Implementation of poverty alleviation action programs and techniques are a systematic and continuous effort in Bangladesh. The object of the paper is to find the main communication challenges of small business in the Bangladesh and give a positive solution or recommendation to our reader through this paper. This report covers all the aspect of the small business to analyze and find the possible help to the reader about the real picture of the communication challenges of small enterprise in the Bangladesh. The limitation of this paper that I use only secondary data because of COVID-19 I Ire not able to interview any businesses hover make an authentic report I added information about the main challenges faced from the internet and have given appropriate reference to complete our paper. Finally, I tried to get some finding of the solution of the communication challenges faced by small business in Bangladesh.